Essentials of children's literature - Lynch-Brown, Carol; Tomlinson, Carl M.; Short, Kathy Gnagey (Boston Pearson, 2011)
Clear, concise, direct narrative that combines lists, examples, figures, and tables with prose make this brief, affordable, straightforward book the perfect guide to sharing literature with children in the classroom. Written by a well-respected author team, this resource is ideal for pre-service and in-service teachers alike, and much appreciated for its wealth of hands-on suggestions and ideas. Selective, up-to-date lists of recommended books are conveniently organized by sub-genre; multicultural and international children's literature is integrated throughout; and an up-dated color insert features recent illustrations from picture books (including examples of computer-generated art) and graphic novels.
Part One. Children and Literature. Chapter 1. Learning about Children and Their Literature -- Chapter 2. Learning about Reading and Literature -- Chapter 3. Learning about Literature -- Part Two. Categories of Literature. Chapter 4. Poetry -- Chapter 5. Picture Books -- Chapter 6. Traditional Literature -- Chapter 7. Modern Fantasy -- Chapter 8. Realistic Fiction -- Chapter 9. Historical Fiction and Biography -- Chapter 10. Informational Books -- Chapter 11. Literature for a Diverse Society -- Part Three. Literature in the School. Chapter 12. Planning the Curriculum -- Chapter 13. Engaging Children with Literature -- Appendixes.
Keywords: Children's literature -- Study and teaching (Higher).; Children's literature -- History and criticism; Children's literature -- Bibliography